Complete Decompression of a Forearm Neonatal Compartment Syndrome Using a Volar Approach: A Surgical Technique. Issue 3 (28th September 2021) - El Beaino, Marc; Connors, Katherine M.; Koehler, Steven M.
Abstract : Fasciotomy of the forearm is a well-described technique for the treatment of compartment syndrome in adults; however, it has not been discussed with sufficient details in the setting of neonatal compartment syndrome. When performing a fasciotomy, it is imperative to decompress all compartments within the forearm to limit the ischemic damage and prevent the progression of the disease. Although it is common to utilize both volar and dorsal incisions to release these compartments, we describe a method that potentially allows for total decompression through a single volar incision with minimal to no morbidity. This novel technique provides sufficient soft-tissue exposure while improving upon the cosmesis that results from a traditional approach.